(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
The practice of using drills shows that the use of a certain type of drills in technologies depends not only on the technological requirements (productivity, grade of the material being processed, accuracy of the holes, etc.), but also on the ratio of the costs of purchasing the tool, main and auxiliary devices and their operation. The reliability of any technical object (in this case, the technological operation of processing a hole) is determined by the number and type of failures that occur in the technological system (in this case, the actual number of failures along the entire technological chain when processing a given hole. Therefore, this article focuses on the “Failure-free operation” of the technological system.